Application of the Semi-Batch Method in Biodiesel Processing Using Refined Bleached Deodorized Palm Oil (RBDPO) with Variations in Feed Addition and Temperature - Indra Muhammad Faizin; Mohammad Prasanto Bimantio; Reni Astuti Widyowanti (Journal of Innovation in Applied Natural Science, 2026)
Background: Biodiesel production efficiency is strongly influenced by reaction method, temperature, and reactant feeding strategy. Semi-batch transesterification offers better molar ratio control and reduced methanol waste compared to conventional batch systems. Aims: This study analyzes the effect of feed addition frequency and reaction temperature on biodiesel efficiency and characteristics using Refined Bleached Deodorized Palm Oil (RBDPO) as raw material. Methods: A Complete Block Design with two factors was applied: feed addition frequency (4×, 5×, 6× per period) and reaction temperature (40°C, 50°C, 60°C) with two replications. Biodiesel was produced using semi-batch transesterification with sodium methylate catalyst. Parameters measured included yield, density, pH, water content, glyceride profile, and methyl ester content. Data were analyzed using Duncan’s Multiple Range Test (5%). Result: The best treatment was 5× feed addition, 50°C, producing the highest methyl ester content (67.18%), yield (92.98%), density (877 kg/m³), pH 6.78, and low water content (1,401 ppm). Most quality parameters approached SNI 7182:2015 biodiesel standards. Conclusion: Semi-batch operation improves conversion control but is not yet fully optimal due to reverse reactions. Further optimization of methanol ratio and reaction time is required to suppress monoglyceride and diglyceride reformation.